Manufacturing in Structural Change in Africa - Nguimkeu, Pierre (World Bank, Washington, DC, 2019)
This paper investigates the scale, causes, and timing of significant episodes of industrialization and deindustrialization in Sub-Saharan Africa. Recent studies have argued that the turning point of manufacturing output and employment shares tends to occur prematurely in this region. The analysis is performed using panel data methods for fractional responses and data from a variety of sources for a panel of 41 African countries. The results overwhelmingly do not support the common finding that Sub-Saharan African countries have begun to deindustrialize. Moreover, the study documents meaningful heterogeneity across Sub-Saharan Africa subregions, with the Southern region being the only subregion to have witnessed deindustrialization. However, this deindustrialization of the Southern subregion does not appear to be occurring prematurely. The study also explores the potential role of the Dutch disease and resource curse hypotheses in understanding Sub-Saharan Africa's manufacturing experience in resource rich countries.